Sequence analysis of the GP5 protein of porcine reproductive and respiratory syndrome virus in Vietnam from 2007 to 2023 - Li, Gan; Li, Yilong; He, Cuihua; Liu, Xiyu; Lv, Chen; Liu, Kexin; Yu, Xingang; Zhao, Mengmeng (Frontiers in Microbiology, 2024)
Introduction Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent 13 of porcine reproductive and respiratory syndrome (PRRS), which is one of the most economically 14 devastating viruses in the Vietnamese swine industry. Methods With a view toward determining the 15 genetic variation among PRRSV strains in Vietnam, we examined 271 PRRSV GP5 protein 16 sequences obtained from strains isolated in Vietnam from 2007 to 2023, for which we constructed 17 phylogenetic trees. Additionally, a collection of 52 PRRSV-1 strains and 80 PRRSV-2 strains 18 isolated in different years were specifically selected for nucleotide and amino acid homology analysis 19 and amino acid sequence alignment. Results The results revealed 76.1%–100.0% nucleotide and 20 75.2%–100.0% amino acid homologies for the PRRSV-1 GP5 gene, and 81.8%–100.0% nucleotide 21 and 81.1%–100.0% amino acid homologies for the PRRSV-2 GP5 gene. Amino acid mutation sites 22 in PRRSV-2 were found to be primarily distributed in the signal peptide region, antigenic sites, two 23 T-cell antigen regions, two highly variable regions (HVRs), and in the vicinity of the neutralizing 24 epitope, with a deletion mutation occurring in the neutralizing epitope, whereas amino acid mutations 25 in the PRRSV-1 sequences were found to occur predominantly in two T-cell epitopes. Genetic 26 analysis revealed that PRRSV-1 strains in Vietnam are of subtype 1 (Global), whereas PRRSV-2 27 strains are categorized into sublineages L1A, L5A, and L8E, with L8E being the predominantly 28 prevalent strain at present. Recombination analyses indicated that no significant recombination 29 events have occurred in any of the assessed 271 Vietnamese PRRSV strains. Discussion Our 30 analyses of 271 Vietnamese PRRSV strains have yielded valuable insights regarding the 31 epidemiological trends and genetic dynamics of PRRSV in Vietnam, and will provide a theoretical 32 basis for formulating prevention and control measures for PRRS and the development of PRRS 33 vaccines.